The Effects of Budesonid that Added to Tiotropium Therapy on Health Related Quality of Life, Exercise Capacity and Pulmonary Functions in COPD Patients - Arslan, Bahar; Turgut, Teyfik (Wolters Kluwer Medknow Publications, 2015)
Objective: The aim of this study was to evaluate the effects of adding inhaled budesonide to the tiotropium treatment on the pulmonary function tests, health-related quality of life and exercise capacity of patients with chronic obstructive pulmonary disease (COPD). Methods: Forty study subjects with COPD were randomized to two groups. The patients in the first group was treated with 1x1 18 mcg of Tiotropium and the patients in the second group was treated with the combination of tiotropium (18 mcg 1x1) and budesonide (400 mcg 2x1) for three months. Pulmonary function tests, six minute walk test, body mass index and Saint George Respiratory Questionnaire (SGRQ) scores were recorded both at the beginning and 3 months later and the results at the begining and third month were compared with each other. There were no statistically significant difference in all basline parameters between the two groups. Results: At the end of the study, no statistically significant differences were obtained between two groups in terms of pulmonary function tests (p>0.05). Significant improvements were observed on the parameters of walking distance (p=0.023) and SGRQ scores (symptom score: p<0.001, activity score: p=0.001, impact score: p=0.003 and total score: p<0.001) in Group 2 when compared with Group 1. Conclusion: These results show that, in patients with COPD, tiotropium/budesonide combination is more effective than alone tiotropium inhalation in quality of life and exercise performance. But this combination is not more effective in improving lung functions.
Keywords: Budesonide; chronic obstructive pulmonary disease; exercise capacity; quality of life questionnaire; tiotropium